Suicidal ideation in older Ghanaian women: The roles of bodily pain, functional limitation, and chronic health conditions. (May 2022) - Muruthi, James R; Spafford, Sarah G; Osa, Maggie L; DeLouize, Alicia; Kowal, Paul; Biritwum, Richard; Snodgrass, J Josh
Background: Although approximately 79% of the world's suicides occur in low- and middle-income countries (LMICs), the limited research in these regions has primarily focused on the rates of suicide attempts (SA) and ideation among men and younger members of the population. Aim: This study investigated the associations between bodily pain, functional limitation, chronic health conditions, and suicidal ideation among older Ghanaian women with a positive screen for depression. Methods: Data was obtained from the World Health Organization's Study on global AGEing and adult health (SAGE) Ghana Wave 1, a nationally representative sample. Based on the interpersonal theory of suicide, we used logistic regression analysis to investigate the associations between the variables. Results: Functional limitation, bodily pain, hopelessness, and hypertension were significantly associated with a higher risk of suicidal ideation after accounting for sociodemographic and other confounding factors. Conclusions: Early interventions designed to decrease hopelessness, hypertension, and functional limitations may lead to reduced suicide ideation among older Ghanaian women who screen positive for depression.